Post-Curing as an Effective Means of Ensuring the Long-Term Reliability of PDMS Thin Films for Dielectric Elastomer Applications - Shamsul, Zakaria; Madsen, Frederikke B.; Skov, Anne Ladegaard (Taylor & Francis, 2017)
Post-curing can be used to facilitate volatile removal and thus produce PDMS films with stable elastic and electrical properties over time. In this study, the effect of post-curing was investigated for commercial silicone elastomer thin-films as a means of improving long-term elastomer film reliability. The Young's moduli and electrical breakdown strengths of commercial (silica-reinforced) PDMS elastomer films, with and without additional 35 parts per hundred rubber (phr) titanium dioxide (TiO2), were investigated after high-temperature (200°C) post-curing for various timespans. The elastomers were found to contain less than 2% of volatiles (significantly higher for TiO2-filled samples), but nevertheless a strong effect from post-curing was observed. The young's moduli as well as the strain-dependent behaviour were found to change significantly upon post-curing treatment where Young's moduli at 5% strain increases with post-cure. Furthermore, the determined dielectric breakdown parameters from Weibull analyses showed that greater electrical stability and reliability could be achieved by post-curing the PDMS films before usage, and this method therefore paves a way towards more reliable dielectric elastomers.